PENGARUH PENGEMBANGAN SUMBER DAYA MANUSIA, PROFESIONALIME KERJA, DAN KOMITMEN ORGANISASI TERHADAP KINERJA ANGGOTA KEPOLISIAN DIT RESKRIMSUS POLDA SULTRA - Ahmad Ashar (Pascasarjana Universitas Halu Oleo, 2022)
This study aims to determine the effect of developing Human Resources, work professionalism and organizational commitment simultaneously positively and significantly on the performance of members of the Dit Reskrimsus Police of the Southeast Sulawesi Regional Police and to determine the partial effect of Human Resources, work professionalism and organizational commitment on the performance of members of the Dit Reskrimsus Police of the Southeast Sulawesi Regional Police.The object of this research is all members of the Dit Reskrimsus Police of the Southeast Sulawesi Regional Police. The population of this research is the police officers who serve in the Dit Reskrimsus Polda Sultra totaling 108 personnel. Determination of the sample using the Slovin formula with a precision of 10% percent thus the research sample amounted to 52 respondents. The research data was collected using a questionnaire, the research data was analyzed using SPSS version 22 to determine the results of the regression analysis of the influence of the independent variable on the dependent variable.The results showed that human resource development, work professionalism and organizational commitment had a positive and significant effect on the performance of members of the Dit Reskrimsus Police of the Southeast Sulawesi Regional Police. From these results it can be concluded that the better Human Resources Development, work professionalism and organizational commitment will be able to improve the performance of members of the Dit Reskrimus Polda Sultra for the better.